PEMBELAJARAN FISIKA DASAR BERBASIS WEB - KS, Monita Monita; Baraja, Abdillah (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
In this era, computer is used to learn many things easily. Because of the lock science lesson which are based on information and technology an interesting and enjoyable learning system is needed. The learning system is based on information and technology. Because it is interesting and enjoyable it will be understood easily. The student will enjoy the lesson because of the interesting techniques. Physic is one of science lessons is is quite difficult for many students to learn it, so interesting tecniques for learning is needed and then the students mativation in joining the lessan will be increased, and last, it will give good impact to the increasing of science development in Indonesia, especially in Physic lesson. The problem statement of this research related to the web based physic lesson is the constuction of intersting and enjoyable physic lesson based on web so thet the students mativation will be increased. The application design is by using Macromedia Dreamweaver 8 in which the use of HTML, programme language, and the use of animation with Macromeida Flash 8. This application is operated with windows based operation through browser Internet Explorer. The use of this application is for the elementary level in which the students learn the basic of physic lesson. It is hoped that this application will be useful for the society, especially the students who learn physic because they will learn physic easily and more atractively. This application is also useful for the school and the teachers because it is a reference. As a reference it is easily understood. It will also give a contribution to the development IPTEK of science and technology information.